Monoclonal antibodies against beta-amyloid protein (lecanemab and donanemab) should not be used in the treatment of Alzheimer's disease - Nitrini, Ricardo; Studart-Neto, Adalberto (Arquivos de Neuro-Psiquiatria, 2025)
Two antiamyloid monoclonal antibodies (mAbs), lecanemab and donanemab, were recently launched for treatment of Alzheimer's disease (AD). These mAbs remove amyloid protein from the brain and cause statistically significant improvement in cognitive/functional tests, meaning a change in evolution of AD. This is important to reinforce the amyloid cascade hypothesis and to further concentrate studies on the pathways from the deposition of the beta-amyloid protein to synaptic loss and neuronal death. However, it is necessary to evaluate whether the results are clinically important. Analysis of the clinical trials showed that the statistically significant differences over placebo did not reach the minimum clinically important difference that would be meaningful for patients, caregivers and clinicians. Besides, the incidence of adverse events is high and potentially severe. Although there are reasons to celebrate this first step towards disease-modifying therapies for AD, lecanemab and donanemab should not be used to treat AD in clinical pratice.
Keywords: Alzheimer Disease; Therapeutics; Antibodies, Monoclonal; Amyloid Cascade; Lecanemab; Donanemab; Minimum Clinically Important Difference